Investigating the Relationship Between Clinical Characteristics, Mental Health, and Vascular Function in Minor Ischemic Stroke or Transient Ischemic Attack Patients - Witid Mitranun; Witoon Mitarnun; Prasit Peepathum; Amorntheap Wandee; Wenika Mitarnun; Wilasinee Pangwong; Tanormsak Senakham (Health Psychology Research)
# Background